SIKAP DAN PERILAKU TENTANG KESEHATAN MATA PADA ANAK PANTI ASUHAN MUHAMMADIYAH DI KOTA MEDAN - HADI NURVAN; ZALDI .; LASZUARNI .; ROBITAH ASFUR (JURNAL ILMIAH SIMANTEK, 2019)
Eyes are organs that is found in every human being. This organ has a very important function in every human. The problems of the health of eyes are still very important for the developed countries and also developing countries especially in Indonesia particularly. Refraction disorders are usually caused by the presence of a factor in the habit of reading too closely so that cause fatigue on eyes (astenopia) and excessive light radiation is received, which are light radiation of computer and television. School environment is being one of the triggers decline sharpness of vision in children, such as reading the existing writings on the board with a distance too far without being supported by lighting adequate classroom, the children read a book at a distance that is too close, and infrastructure of the school that are not ergonomic when teaching and learning process. The purpose of this research is to know the description of attitudes and behaviours towards healthy eyes in children orphanage of Muhammadiyah in Medan. Methods: The type of research used in this study is cross sectional research with quantitative approach. The sample of this research is as much as fifty childrens of junior level and vocational school level Muhammadiyah in an orphanage in the city of Medan. Results: Respondents with normal visus that have good attitude and behavior are two subjects, moderate with twentysix subjects, and less with two subjects, while the respondents with abnormal visus that have good attitude and behavior are four subjects, moderate with eleven subjects, and less with five subjects. Conclusion: The overview of attitude and behavior toward eye health of Muhammadiyah orphanage in Medan City are generally in the moderate category.